Comparaison des approches histologiques et micro-tomographiques pour l’étude de la diagenèse osseuse - Lolita Trenchat; Nicolas Vanderesse; Éric Pubert; Yannick Lefrais; Katrien Van de Vijver; Sacha Kacki; Eline M.J. Schotsmans (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Histology is a conventional but destructive technique for investigating bone diagenesis. Micro-tomography is a non-destructive technique that can also be used to investigate diagenetic alterations. The aim of this study is to evaluate the benefits and limitations of these two methods by analysing bone diagenesis to determine if micro-tomography (non-destructive) can be more beneficial than histology (destructive), and if scoring can be quantified in both methods. Therefore, bone samples from six individuals from the churchyard of St. Anne (1833-1916) in Koekelberg (Belgium) were analysed. Each thin section and scan was qualitatively scored with the Oxford Histological Index and quantitatively assessed through image analysis. The results show that micro-tomography allows assessment of degradation of the scanned bones without destruction. This is impossible with histology where analysis is restricted to a small cross-section. On the other hand, histology brings more detail to the bone microstructure thanks to its finer resolution. Overall, this study demonstrates that both methods provide different but complementary information about bone diagenesis and stresses the importance of using quantifying methods to analyse diagenetic alterations.